2004
DOI: 10.1088/0022-3727/37/22/015
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurements of the thermal optical and linear thermal expansion coefficients of a thin film etalon from the reflection spectra of a super-luminescent diode

Abstract: An experimental determination technique for simultaneous measurements of the thermal optical and linear thermal expansion coefficients of tantalum pentoxide thin films in the infrared wavelength region is described. A tantalum pentoxide thin film deposited directly onto the end face of a single mode optical fibre is illuminated by a super-luminescent diode source and its spectrum on reflection, between 1460 and 1620 nm, is monitored at various temperatures using an optical spectrum analyser. Temperature induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In some cases, there has even been some controversy regarding some measurements. In the case of the CTE, measurements have ranged from −4.4 × 10 −5 K −1 for ion-assisted e-beam sputtered tantala [8], to 2.4×10 −6 K −1 for IBS tantala [9]. Measurements made by Braginsky and Samoilenko [10] suggested that the CTE of tantala was roughly (5 ± 1) × 10 −6 K −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, there has even been some controversy regarding some measurements. In the case of the CTE, measurements have ranged from −4.4 × 10 −5 K −1 for ion-assisted e-beam sputtered tantala [8], to 2.4×10 −6 K −1 for IBS tantala [9]. Measurements made by Braginsky and Samoilenko [10] suggested that the CTE of tantala was roughly (5 ± 1) × 10 −6 K −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous measurements of the thermorefractive properties of Ta 2 O 5 have produced results for β that vary by about two orders of magnitude. The published values of β include 2.3 × 10 -6 [30], 4.76 × 10 -5 [31], and 1.21 × 10 -4 [32]. Differences in deposition methods or annealing conditions may result in differing values for β but some of this variation may be due to temperatureinduced coating stress.…”
Section: Contribution To β From Temperature-induced Coating Stressmentioning
confidence: 99%
“…Values of refractive index and extinction coefficient may vary depending on the fabrication technique used. Optical characterization (Inci, 2004) of the reflection response of a Ta 2 O 5 film deposited by electron beam evaporation on the cleaved end-face of a single-mode optical fiber made it possible to measure a TOC of about 1.21 × 10 24 K 21 around 1550 nm.…”
Section: Tantalum Pentoxide (Ta 2 O 5 )mentioning
confidence: 99%